2019
DOI: 10.4081/or.2019.7795
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Positioning of the Ulnar Nerve Found During Carpal Tunnel Release: A Case Report

Abstract: Introduction: Aberrant positioning of the ulnar nerve volar to the transverse carpal ligament is a rare anatomic variation.Case Presentation: We present the case of a 55-year-old female with unique ulnar nerve anatomy that was discovered introperatively during carpal tunnel release.  The ulnar nerve was running directly adjacent to the median nerve in the distal forearm and as the median nerve traversed dorsal to the transverse carpal ligament (flexor retinaculum) to enter the carpal tunnel the ulnar nerve con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Abnormal route of ulnar nerve has been described. It has been found to run directly adjacent to the median nerve in the distal forearm during carpal tunnel release surgery [20]. In a published analogous case, ulnar nerve exploration after distal radius fracture dorsally malunited, revealed that the nerve was in touch with the subcutaneous ulnar surface, fixxed by a fibrous tether 5 cm proximal to the ulno-carpal joint line suggesting an anatomical variation and not post-traumatic scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal route of ulnar nerve has been described. It has been found to run directly adjacent to the median nerve in the distal forearm during carpal tunnel release surgery [20]. In a published analogous case, ulnar nerve exploration after distal radius fracture dorsally malunited, revealed that the nerve was in touch with the subcutaneous ulnar surface, fixxed by a fibrous tether 5 cm proximal to the ulno-carpal joint line suggesting an anatomical variation and not post-traumatic scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of this anatomical variation and adequate visualization of the UN, along with the surrounding structures, is crucial to avoid iatrogenic injuries during carpal tunnel release. 48,49 There are also cases of aberrant transligamentous sensory branches of the UN entering the distal transverse carpal ligament. Hand surgeons should be aware of this anatomical variation because its location puts it at risk of iatrogenic injury during open and endoscopic carpal tunnel release.…”
Section: Most Variations Of the Un Occur In The Hand Regionmentioning
confidence: 99%
“…Awareness of this anatomical variation and adequate visualization of the UN, along with the surrounding structures, is crucial to avoid iatrogenic injuries during carpal tunnel release. 48 49 …”
Section: Ulnar Nervementioning
confidence: 99%